Vaksin Kolera Di Tanah Kolonial: Upaya Pengendalian Penyakit Di Kota-Kota Besar Di Jawa, 1910-1912 - Faishal Sahru Rhamadan, Faishal; Rochwulaningsih, Yety; Sudarsih, Sri (PURBAWIDYA, 2025)
This study examines the implementation of cholera vaccination programs in Java between 1910 and 1912 through a qualitative historical approach based on a comprehensive review of primary and secondary sources, verified both internally and externally. It explores the development and administration of cholera vaccines among the population of the Dutch East Indies in the early twentieth century. The findings indicate that Java were highly vulnerable to cholera outbreaks, recording 72,013 cases and 56,309 deaths (73.7%) in 1910, primarily in major urban centers such as Semarang, Surabaya, Batavia, and Pasuruan. A.H. Nijland, Director of the Pasteur Institute, significantly advanced cholera vaccine research and advocated mass immunization as a governmental public health strategy. Following his recommendation, the colonial administration launched a large-scale vaccination campaign across endemic areas beginning in 1910. This initiative effectively reduced both incidence and mortality, with reported cases decreasing to approximately 9,500 and a mortality rate of 56.5% by 1911. The study concludes that mass vaccination represented a pivotal epidemiological intervention in mitigating cholera transmission and improving public health outcomes in the Dutch East Indies.